'Let Margaret Sleep': putting to bed the authorship controversy over Sister Peg. Issue 2 (17th February 2023) - Sher, Richard B.
ABSTRACT: Nearly four decades after David Raynor attributed to David Hume an allegorical Scots militia pamphlet from the early 1760s popularly known as Sister Peg, there is still no scholarly consensus about whether the author was in fact Hume or his friend Adam Ferguson. Using new evidence that has emerged since the appearance of Raynor's edition in 1982 – including information about Sister Peg 's publication history, Ferguson's handwritten corrections and revisions in the Abbotsford copy of the work, a 1767 newspaper article by James Boswell and a copy of a 1775 letter by Sir John Dalrymple that both named Ferguson as the author, two volumes of Ferguson's correspondence published in 1995, and a recently discovered letter by Ferguson from 1809 – this article seeks to resolve this controversy by establishing that Sister Peg was written by Ferguson, as his fellow militia agitator Alexander Carlyle asserted in his memoirs. In the process, the article refutes Raynor's arguments about Ferguson's supposed incapacity for writing a satirical pamphlet like Sister Peg and clarifies the nature of Hume's views and actions in regard to the Scots militia cause during the Seven Years' War. The article also throws light on several related issues affecting Hume and Ferguson's circle.